Pengaruh Penambahan Tepung Maggot Black Soldier Fly Dengan Konsentrasi Berbeda Terhadap Sifat Fisik Dendeng Daging Ayam - Rahman, Ali; Utama, Dicky Tri; Hidayati, Yuli Astuti; Marlina, Eulis Tanti (Jurnal Teknologi Hasil Peternakan, 2025)
Dendeng is a type of processed meat that combinescuring and drying processes. Dendeng has potential in efforts todiversify food products, one of which is by adding Black SoldierFly (BSF) maggot meal. BSF maggot meal is a sustainable source ofprotein that has the potential to meet future protein needs. Thisstudy aimed to determine the effect and best addition level of BSFmaggot meal on yield, pH, tenderness, and color of chickendendeng. The study was conducted experimentally using acompletely randomized design. There were four levels of addition,0%, 5%, 10%, and 15% with five replications. The data is processedusing analysis of variance and if the results have a significant effect,it is continued with the Duncan distance test. The results showedthat the addition of BSF maggot meal had a significant effect on pHand color (P<0.05) without affecting the yield and tenderness ofchicken jerky (P>0.05). The addition of 5% BSF maggot mealresulted in good physical quality of chicken dendeng with atenderness value of 13.96 N, yield of 83.55%, pH of 5.85, and color(L* 43.08; a* 4.25; b* 18.61; C* 19.09; and h° 1.34).